Malaysia’s China Policy and the South China Sea Dispute Under the Najib Administration (2009–2018): A Domestic Policy Process Approach - Ngeow, Chow Bing (Wiley, 2019)
The past explanations of Malaysia’s policy responses to China’s assertiveness in the South China Sea centered on systemic, economic, and ideational factors. I adopt a different approach by looking into the decision-making process of Malaysia’s China policy during Najib Razak’s administration (2009–2018). I explain that the China policy decision-making process under Najib was divided into two channels, one focusing on nonsecurity matters and the other on security matters, with the prime minister seated at the top of the two channels, while there were very little interactions between the two channels. These characteristics could partially explain the nature and outcome of Malaysia’s South China Sea policy posture. © 2019 Policy Studies Organization